2012
DOI: 10.1007/s00468-011-0675-2
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the radial growth and wood density components in relation to cambial age in 30-year-old Pinus brutia Ten. at two test sites

Abstract: Radial growth and wood density are important traits in assessing wood quality. Our objective was to investigate patterns of variation of radial growth (ring width, earlywood width, latewood width, latewood proportion) and wood density (ring average density, earlywood density, latewood density) components in a 30-year-old Pinus brutia at two test sites in Turkey. Wood increment cores at a height of 1.30 cm (dbh) from 1,010 trees at age 30 years were evaluated at two test sites. The radial growth and wood densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
3
27
0
1
Order By: Relevance
“…The results obtained in this and other studies regarding growth components are compiled in Tab Comparing to other softwood species, the RW values of Scots pine wood obtained in this study were similar to those found in Pinus brutia, Abies balsamea, and Pinus pinaster, ranging from 2.06 to 3.51 mm (Louzada 1991, 2000, Koga & Zhang 2004, Guller et al 2012. Exceptions were found for Picea mariana (4.03 mm) and Pinus pinaster (4.22 to 5.13 mm) in younger trees with ages from 15 to 18 years (Zhang & Jiang 1998, Louzada & Fonseca 2002, Gaspar et al 2008a.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 83%
See 2 more Smart Citations
“…The results obtained in this and other studies regarding growth components are compiled in Tab Comparing to other softwood species, the RW values of Scots pine wood obtained in this study were similar to those found in Pinus brutia, Abies balsamea, and Pinus pinaster, ranging from 2.06 to 3.51 mm (Louzada 1991, 2000, Koga & Zhang 2004, Guller et al 2012. Exceptions were found for Picea mariana (4.03 mm) and Pinus pinaster (4.22 to 5.13 mm) in younger trees with ages from 15 to 18 years (Zhang & Jiang 1998, Louzada & Fonseca 2002, Gaspar et al 2008a.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 83%
“…Lower wood densities were found for other resinous trees, namely Pinus brutia, Abies balsamea and Picea mariana, with values ranging from 351 to 495 kg m -3 (Zhang & Jiang 1998, Koga & Zhang 2004, Guller et al 2012. Although the Portuguese Scots pine stands are somewhat older (average of 55 years) than the remaining stands of other species (15 to 38 years), there is a tendency for Pinus sylvestris growing in Portugal to have slightly denser wood than resinous trees from other regions.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 83%
See 1 more Smart Citation
“…Tracheid length and diameter increase rapidly in a non-linear way during the juvenile phase and afterwards more gradually in mature wood. Wood density results were consistent with previous observations in conifers increasing with the cambial age linking this pattern to the thickness of the cell wall as the tree becomes older (Guller et aL, 2012) In our case, the southern site follows the theoretical pattern (low values at the beginning of life and growing until stable values), meanwhile, a delay in the time of wood maturation seems to occur further north showing the longest period in the juvenile stage and a late change to mature wood especially for tracheid diameter ( Figure 13). This observation along the altitudinal gradient may be due to temperature associated with soil depth and genetic differences due to natural selection (Grossnickle, 2000).…”
Section: Comparison Between Agessupporting
confidence: 91%
“…The average annual growth ring width is supposed to tend to a constant value after 16 years. This hypothesis for normal wood can be observed for other species in literature (Adamopoulos et al 2010;Guller et al 2012;Campelo et al 2015). Notice that for this study, the model will not be used for trees older than 16 years old.…”
Section: Annual Growth Ring Widthmentioning
confidence: 68%